2020
DOI: 10.3390/sports8080114
|View full text |Cite
|
Sign up to set email alerts
|

No Effects of New Zealand Blackcurrant Extract on Physiological and Performance Responses in Trained Male Cyclists Undertaking Repeated Testing across a Week Period

Abstract: Anthocyanin supplements are receiving attention due to purported benefits to physiological, metabolic, and exercise responses in trained individuals. However, the efficacy of anthocyanin intake over multiple testing days is not known. We compared a placebo and two doses of anthocyanin-rich New Zealand blackcurrant (NZBC) extract (300 and 600 mg·day−1) on plasma lactate, substrate oxidation, and 16.1 km time trial (TT) performance on three occasions over 7-days in a fed state (day 1 (D1), D4, and D7). Thirteen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 46 publications
0
18
0
1
Order By: Relevance
“…The study was designed to allow a detection of 2-3 % difference in 16.1 km time-trial performance (1 − β =0.80: 0.05 =α level) (Cook et al, 2015). Data on blood lactate, substrate oxidation and TT performance are reported elsewhere (Montanari et al, 2020). Cardiovascular data at rest and during submaximal exercise were checked for homogeneity with the Mauchly test of sphericity and adjusted with the Greenhouse-Geisser test if violations were present.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study was designed to allow a detection of 2-3 % difference in 16.1 km time-trial performance (1 − β =0.80: 0.05 =α level) (Cook et al, 2015). Data on blood lactate, substrate oxidation and TT performance are reported elsewhere (Montanari et al, 2020). Cardiovascular data at rest and during submaximal exercise were checked for homogeneity with the Mauchly test of sphericity and adjusted with the Greenhouse-Geisser test if violations were present.…”
Section: Discussionmentioning
confidence: 99%
“…The latter study showed that a sample of 9 would be needed to detect a difference of 20% in CO. For the present study, however, cardiovascular responses were not selected as primary outcomes. Data collected were part of a wider study project which included additional physiological (lactate levels, substrate oxidation) and performance parameters (16.1 km TT) as primary outcomes (Montanari et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of anthocyanins on nitric oxide biomarkers, vascular function, muscle oxygenation, and performance were examined in 11 studies [ 15 , 18 , 23 , 28 , 29 , 30 , 38 , 39 , 40 , 41 , 42 , 43 ]. Two studies evaluated nitric oxide biomarkers and vascular function.…”
Section: Fruit-derived Anthocyanins On Cycling-induced Responses and ...mentioning
confidence: 99%
“…In another study, the protocol consisted of an incremental intensity cycling test followed by 10 min cycling at 65% VO 2max ending with the 16.1 km time trial. Between each test, participants rested for 15 min [ 43 ]. Another study was performed with 2 × 4 km time trials separated by 10 min of active recovery at the selected auto cycling intensity [ 30 ] and one with two incremental cycling protocols with the recording of physiological and cardiovascular responses [ 42 ].…”
Section: Fruit-derived Anthocyanins On Cycling-induced Responses and ...mentioning
confidence: 99%